Cycloartobiloxanthone, a Flavonoid with Antidiabetic, Antibacterial and Anticancer Activities from Artocarpus kemando Miq. - Tati Suhartati; Antin S. Prihatin; Armidla N. Kurniati; Hendri Ropingi; Yandri Yandri; Sutopo Hadi (Emerging Science Journal, 2024)
In this present work, a cycloartobiloxanthone compound was isolated from the stem wood and root bark of the Pudau plant (Artocarpus kemando Miq.). The purity of the compound was determined using thin-layer chromatography with three eluent systems and melting point tests. The sample was then analyzed using UV-Vis, IR, and NMR spectroscopy, ensuring that the compound is cycloartobilox-anthone. The cycloartobiloxanthone compound was obtained in a yellow crystalline form with a melting point of 285.1-294°C. The compound was then investigated for antidiabetic, anticancer, and antibacterial properties, showing that the compound has an anti-diabetic effect by reducing the activity of the α-amylase enzyme, with the highest percentage of inhibition of 48.53 ± 1.84% achieved with the use of 1000 ppm of the compound. Cycloartobiloxanthone isolated has an IC50 value of 9.21 µg/mL for anticancer activity against MCF-7 cells, indicating that the compound shows active cytotoxic actions. Staphylococcus aureus was very strongly inhibited by the compound in the antibacterial test at all doses, whereas for Salmonellasp., the activity was categorized as moderate at concentrations of 0.4 and 0.3 mg/disc and strong at 0.5 mg/disc. The anti-diabetic, anti-cancer, and antibacterial bioactivity studies indicated that the cycloartobiloxanthone compound isolated has a broad spectrum of pharmacological actions, indicating that the compound has promising potential. Doi: 10.28991/ESJ-2024-08-01-04 Full Text: PDF